2014
DOI: 10.12976/jib/2014.2.20
|View full text |Cite
|
Sign up to set email alerts
|

Patterns in Orthoptera biodiversity. I. Adaptations in ecological and evolutionary contexts

Abstract: The Orthoptera have inhabited the Earth for ca 300 million years and today include about 25,000 described species. Although orthopterans are mainly known to the general public by their most conspicuous species such as rangeland grasshoppers, locusts, katydids and crickets, they include an amazing diversity of forms and life-styles. In this review, I bring together a series of facts about orthopteran biology that demonstrate their enormous biodiversity, concentrating on ecological and evolutionary characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 220 publications
1
21
0
1
Order By: Relevance
“…As the diet of pygmy grasshoppers generally consists of algae, moss, fungi and lichen that thrive on wetter conditions (Paranjape et al 1987, Hochkirch et al 2000, Kočárek et al 2008, Bidau 2014, Kuřavová and Kočárek 2015, Kuřavová et al 2017a, our findings also suggested that greater abundance of food sources in wetter microhabitats can account for higher abundance of pygmy grasshoppers in general. We also found that specifically, the wetness of dicot leaf litter is strongly positively correlated with the abundance of pygmy grasshoppers.…”
Section: Discussionsupporting
confidence: 56%
“…As the diet of pygmy grasshoppers generally consists of algae, moss, fungi and lichen that thrive on wetter conditions (Paranjape et al 1987, Hochkirch et al 2000, Kočárek et al 2008, Bidau 2014, Kuřavová and Kočárek 2015, Kuřavová et al 2017a, our findings also suggested that greater abundance of food sources in wetter microhabitats can account for higher abundance of pygmy grasshoppers in general. We also found that specifically, the wetness of dicot leaf litter is strongly positively correlated with the abundance of pygmy grasshoppers.…”
Section: Discussionsupporting
confidence: 56%
“…Orthoptera (grasshoppers, locusts, and bush crickets) is an abundant and species‐rich order that occurs from sea level up to almost 5,000 m above sea level (a.s.l. ; Alexander , Bidau ). We thereby focused not only on body size, which is related to fecundity, but also on morphological traits that are related to dispersal (wing length), jumping ability (hind femur length), and predator detection (eye size).…”
Section: Introductionmentioning
confidence: 99%
“…Among Orthoptera, we can distinguish carnivorous (part of Tettigonioidea), omnivorous (especially Grylloidea) and herbivorous (Acridoidea, Tetrigoidea and part of Tettigonioidea) food strategies. Most species are generalists, and their specialization to some taxon of plant or animal food is rare (Gangwere ; Bidau ). Various environmental factors, e.g.…”
Section: Introductionmentioning
confidence: 99%